MOLECULAR DOKING AND ADMET STUDIES OF AMINO-PYRIMIDINE DERIVATIES AS MYCOBACTERIUM TUBERCULOSIS SER/THR PROTEIN KINASES B INHIBITORS - Khamouli1, S; Belaidi, S; Lanez2, T (university of eloued -جامعة الوادي, 2019)
We used the molecular docking method with Molegro software and we calculate ADME-T properties using Marvin Sketch and preADMET. The 29 amino-pyrimidines ligands were examined for docking studies with PknB (PDB Code: 2FUM).The Moldock score of the best three ligands L9, L12 and L21 are-161.475, -152.003 and-143.359 Kcal/Mol. These percentage shows that these candidature ligands have high binding energy percentage than the native MIX ligand. The ligand L21 has the human intestinal absorption (HIA), Caco-2 cell permeability, and plasma protein binding values of 85.48, 6.312 (nm/Sec.) and 93.097% respectively, which are comparable to MIX and the other ligands L9, L12. This computational study helped to prove that the ligand L21 have the ability to kill the Mycobacterium tuberculosis by inhibiting the expression of protein kinase B.
article
Keywords: Amino-pyrimidine, Tuberculosis, PknB, Molecular docking, ADMET